An optimized structure for enhancing optical absorption of solar energy inelliptical gaAs nanowire array solar cell - Sakib, Nazmus; Ahad, Md. Atiqur Rahman (Penerbit Universiti Kebangsaan Malaysia, 2018)
The enhanced optical absorption of solar energy in a solar cell using nanostructured materials is a very demanding and important research area. Hence, an optimized structure to increase the optical absorption of solar energy in an elliptical GaAs (Gallium Arsenide) nanowire array solar cell was proposed in this paper. The influence of geometric parameters on the optical absorption of elliptical GaAs nanowire solar cells was investigated by exploiting the finite difference in time domain simulations. Based on the design and analysis, the elliptical GaAs nanowire array performed better than any circular GaAs nanowire. It was found that the enhanced performance was due to the reduced reflection from the top surface and a reduced transmission from the bottom surface of the elliptical GaAs nanowire array. The structural parameters of the elliptical GaAs nanowire were optimized by calculating the short circuit current density (Jsc) for different geometries over the solar spectrum. It was demonstrated that there was an increase of 9.4% in the Jsc compared with the circular GaAs nanowire under the optimized conditions.